BRAF V600 Mutation Profile of Metastatic Melanoma in the Thrace Region of Turkey - Nuray CAN; Ebru TAŞTEKIN; Tülin DENIZ YALTA; Necdet SÜT; Selma KORKMAZ; Ufuk USTA; Fulya ÖZ PUYAN; Ezgi GENÇ; Mert CEZIK; Busem BINBOĞA TUTUĞ; Osman KÖSTEK; Hilmi TOZKIR (Federation of Turkish Pathology Societies, 2018)
Objective: BRAF is the most common mutation in melanoma. The most common subtype is BRAF V600E, followed by V600K. Initially, the authors aimed to investigate whether clinicopathological features of melanoma are associated with BRAF mutations. We then aimed to present the relationships between the clinicopathological features and the mutated subtype (V600E vs V600K). Material and Method: 61 patients with metastatic malignant melanoma (affecting the lymph node or other distant sites) were selected. Patient data regarding age at the time of diagnosis, sex, metastatic site (lymph node, distant metastasis or both) and primary tumour site were obtained from the hospital's database. Tissue samples containing at least 30% tumour cells were isolated from the specimens of 61 patients (24 samples from primary tumours and 37 from metastatic foci) for BRAF analysis. Comparisons between the BRAF V600 mutation and clinicopathological and histopathological features were performed. Results: BRAF V600 mutation was detected in 34 (55.7%) patients. The subtype was BRAF V600E in 22 (64.7%) patients, BRAF V600K in 11(32.4%) patients and BRAF V600R in 1(2.9%) patient. The crucial results of the present study may be summarized as follows: i) BRAF V600 mutation was more common in older patients and tumors with BRAF V600 mutation revealed necrosis and LVI more commonly than wild-type tumors, ii) BRAF V600K mutation was more common in older patients and BRAF V600K mutated tumors exhibited ulceration more commonly than tumors with BRAF V600E mutation (close to significant). Conclusion: The BRAF V600 mutation may have interactions with prognostic clinicoptahological features of melanoma including necrosis and lymphovascular invasion. V600K mutation may be more common than expected and may have different associations with properties of the tumor such as tumor ulceration and patient age. Investigation of the mutated subtype of the BRAF gene may therefore reveal more detailed data about the management of melanoma and may also prevent missing of candidates for BRAF inhibitor therapies.